2007
DOI: 10.1111/j.1742-7843.2007.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro Inhibitory Potential of Trade Herbal Products on Human CYP2D6‐Mediated Metabolism and the Influence of Ethanol

Abstract: Abstract:The six commonly used trade herbal products, St. John's wort, common valerian, common sage, Ginkgo biloba , Echinacea purpurea and horse chestnut, and ethanol, were investigated for their in vitro inhibitory potential of cytochrome P450 2D6 (CYP2D6)-mediated metabolism. Herbal components were extracted from commercially available products in a way that ensured the same composition of constituents in the extract as in the original trade products. c-DNA baculovirus expressed CYP2D6 was used with dextrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
(51 reference statements)
3
34
0
Order By: Relevance
“…Curiously, it has previously been reported that ethanol can also have a biphasic effect on CYP2D6 activity. Increasing CYP2D6 activity occurs at low EtOH concentrations (1.1% ethanol is able to increase CYP2D6 activity by 175% relatively to the control) but at higher concentrations, EtOH causes a linear inhibition of the activity of this isoenzyme (Hellum and Nilsen, 2007). In accordance with this fact, an increase in CYP2D6 activity in chronic ethanol consumers was previously described (Eisenburg et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
“…Curiously, it has previously been reported that ethanol can also have a biphasic effect on CYP2D6 activity. Increasing CYP2D6 activity occurs at low EtOH concentrations (1.1% ethanol is able to increase CYP2D6 activity by 175% relatively to the control) but at higher concentrations, EtOH causes a linear inhibition of the activity of this isoenzyme (Hellum and Nilsen, 2007). In accordance with this fact, an increase in CYP2D6 activity in chronic ethanol consumers was previously described (Eisenburg et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
“…This could lead to decreased efficacy or increased toxicity (7,8) . Owing to the complex matrix of phytochemical constituents the probability of affecting the pharmacodynamic and/or pharmacokinetic profi le of a concomitant drug is high, therefore caution should be employed in dual usage (8) . Although research is available concerning the interactions of some herbal preparations, it is limited and not always well-defi ned, and even less so for indigenous African herbal remedies.…”
Section: Introductionmentioning
confidence: 98%
“…This could be explained by non-genetic factors having been shown to reduce CYP2D6 expression and/or activity. 17,18 On the other hand, limitations in phenotype measurement could also contribute to these discrepancies. Indeed, in contrast to the PM phenotype, where a DEM MR antimode can be precisely defined, the definition for the IM and UM phenotype is less clear.…”
Section: Genotype-phenotype Associationmentioning
confidence: 99%